Long-term assessment of enriched housing and subventricular zone derived cell transplantation after focal ischemia in rats - Rissanen, Anna; MacLellan, Crystal L.; Chernenko, Garry A.; Corbett, Dale (My University, 2008)
The potential for using stem cells to treat stroke has garnered much interest, but stem cell therapies must be rigorously tested in animal models before transplantation studies progress to clinical trials. An enriched environment enhances transplanted subventricular zone (SVZ) cell migration and functional benefit following stroke in rats. However, the ability of SVZ cells to survive, migrate, differentiate and promote functional recovery at protracted survival times (e.g., 3 months) has not been investigated. The vasoconstrictive peptide endothelin-1 was injected adjacent to the middle cerebral artery to produce focal ischemia. Seven days later, cells derived from the SVZ of adult mice (800,000 cells/rat or vehicle injection) were transplanted into the sensory-motor cortex and striatum, and rats were then housed in enriched or standard conditions. Rats in enriched housing had access to running wheels once per week. Recovery was assessed in the forelimb-use asymmetry task (cylinder) at 1, 2, or 3 months after transplantation immediately prior to euthanasia. Transplanted cell survival and migration were quantified using stereology. Cell phenotype was determined with immunohistochemistry and confocal microscopy. Enriched housing did not enhance survival or migration of transplanted SVZ cells at protracted survival times, and the majority (~ 99%) of cells died within 2 months of transplantation. Cell survival was significantly, and negatively, correlated with microglial activation. Many surviving cells expressed an astrocytic phenotype. Functional recovery was not improved at any time. Therapies involving transplantation of SVZ cells following stroke must be further optimized in order to enhance long-term cell survival and thereby maximize functional benefit.
Keywords: stroke; enriched environment; stem cell transplantation; cell survival; functional recovery